An Analysis Students’ Anxiety in Speaking English - Yanti, Dawi; Megawati, Eka (Indonesian Research Journal on Education, 2025)
The primary objective of this study was to identify the levels of speaking anxiety among students at STT Migas Balikpapan, with a specific focus on Geology Engineering students. Speaking is often regarded as one of the most challenging skills to master in English language learning, particularly for EFL learners, due to its unpredictable nature and the real-time processing it demands. The method of the research is a qualitative design was employed, utilizing a closed-ended Likert-scale questionnaire to gather data from 30 participants. The analysis revealed that a significant proportion of students experience varying degrees of anxiety, with 50% classified as anxious or very anxious. Key factors identified include low self-confidence, fear of negative evaluation, and limited exposure to authentic speaking situations. The findings underscore the necessity for educators to foster a supportive classroom environment and implement strategies to alleviate anxiety, thereby enhancing students' speaking performance. This research contributes to the existing literature on language anxiety and provides valuable insights for future studies aimed at addressing speaking anxiety in EFL contexts.